Stress monitoring and impact bearing capacity of circular concrete-filled steel tubular short columns under axial impact loads. Issue 3 (February 2020) - Li, Zhao; Gao, Jingwei; Xu, Jindong; Du, Guofeng
Compared with the traditional reinforced concrete columns, the concrete-filled steel tubular columns with a better restraint effect of steel tube on core concrete showed higher bearing capacity and ductility under static loads. However, except static loads, concrete-filled steel tubular columns are commonly exposed to the extreme dynamic loads including earthquake, explosion, and impact. The study on dynamic behavior of concrete-filled steel tubular columns is extremely significant to ensure their safety against such dynamic loads. In this article, a polyvinylidene fluoride piezoelectric smart sensor was proposed to monitor the axial impact bearing capacity of specimen based on stress monitoring under impact loads. The concrete-filled steel tubular columns with smart sensor embedded were tested, which considered the effects of both hammer impact heights and steel tube thickness on the axial impact bearing capacity. The impact bearing capacity calculated based on the monitoring results of polyvinylidene fluoride sensor is in good agreement with the measured values, which verifies the feasibility of this method. Moreover, it is found that the failure mode of concrete-filled steel tubular short columns is the local tearing failure or local buckling. In addition, non-linear finite element models were also established to study the effect of different parameters on the axial bearing capacity. The simplified formula for calculating the axial impact bearing capacity of concrete-filled steel tubular short columns was proposed based on the large amount verified model. Through the comparison between the calculation value and the test value, the formula is found to well reflect the axial impact bearing capacity of concrete-filled steel tubular short columns, which provides a reference for similar research.